2008
DOI: 10.1161/circulationaha.107.738229
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Mapping of the Left Ventricle in a Porcine Model of Chronic Myocardial Infarction With Magnetic Resonance–Based Catheter Tracking

Abstract: Background-X-ray fluoroscopy constitutes the fundamental imaging modality for catheter visualization during interventional electrophysiology procedures. The minimal tissue discriminative capability of fluoroscopy is mitigated in part by the use of electroanatomic mapping systems and enhanced by the integration of preacquired 3-dimensional imaging of the heart with computed tomographic or magnetic resonance (MR) imaging. A more ideal paradigm might be to use intraprocedural MR imaging to directly image and guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…As discussed, there are significant concerns regarding RF safety for long transmission lines, while they must remain capable of conducting μV heart volume at the beginning of the procedure, and then to display the location within a segmented chamber of the volume (see Figure 4). 28,34,35 Manual or automated chamber segmentations have both been employed to provide an interface that closely mimics the strengths of a clinical EAM system. Passive and active tracking sequences may be interleafed, providing real-time location updates with visualisation of device position and surrounding anatomy, and the passive imaging slice position can be coordinated with catheter tip position.…”
Section: Active Tracking Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, there are significant concerns regarding RF safety for long transmission lines, while they must remain capable of conducting μV heart volume at the beginning of the procedure, and then to display the location within a segmented chamber of the volume (see Figure 4). 28,34,35 Manual or automated chamber segmentations have both been employed to provide an interface that closely mimics the strengths of a clinical EAM system. Passive and active tracking sequences may be interleafed, providing real-time location updates with visualisation of device position and surrounding anatomy, and the passive imaging slice position can be coordinated with catheter tip position.…”
Section: Active Tracking Sequencesmentioning
confidence: 99%
“…Figure 4). 35 They went on to investigate realtime visualisation of lesion formation, 48 a challenging area that has also been investigated by a group in Utah, USA. …”
Section: Electrogram Fidelitymentioning
confidence: 99%
“…Inhomogeneous scarring with varying degrees of subendocardial myocardial fiber preservation within dense zones of fibrosis results in slowed conduction, nonuniform anisotropy, and the presence of conduction channels leading to re-entrant VT. 53,54 Having superb imaging quality with high temporal and spatial resolution in even the most challenging patients, CMR provides excellent visualization and characterization of substrate. The most useful technique is late Figure 6.…”
Section: Cardiac Mri Tissue Characterizationmentioning
confidence: 99%
“…First studies reported on feasibility of real-time MRI for catheter guidance in diagnostic electrophysiology studies 10 and electroanatomic mapping with magnetic resonance-based catheter tracking. 11 Just recently, even complex electrophysiological interventions such as AV modulation 12 and isthmus ablation 13 under magnetic resonance guidance have been performed using a magnetic resonance-conditional electrophysiology setup.…”
Section: Clinical Perspective On P 294mentioning
confidence: 99%